Behavioural design protocols in architectural design studios: a microscopic analysis - Rahimian, Farzad Pour; Ibrahim, Rahinah (Universiti Putra Malaysia Press, 2013)
Due to the emerging complicated global design problems, new design research methodologies need to analyse the structures and processes of design cognition for discovering multi-aspect and multi-variable design strategies. Adapting such objective methods of design assessment, as opposed to the traditional survey based subjective methods of design performance studies, is therefore essential for improvements of design education in rapidly developing Malaysian design schools. This paper proposes Protocol Analysis Methodology for facilitating microscopic study of educational design performance assessment. Protocol Analysis has become the most prevailing research methodology for design research over the last two decades; and can be considered as a reliable methodology due to its objectiveness and accuracy in studying designers’ cognitive actions. This paper illustrates how the protocol analysis methodology was used in one experiment for comparing designers’ creativity when working with two types of design media, namely, traditional sketching and Virtual Reality 3Dimentional sketching. In this study, a descriptive statistical analysis on protocol data conveyed insight into novice designers’ cognitive protocols microscopically in form of various charts and graphs. Results offered objective insights into the changes in the design process that were associated with applying different design media. This paper presents background literature, explains the conducted protocol analysis experiment, and presents results from the protocol data to reveal designers’ action and thought protocols. This paper also recommends the application of protocol analysis methodology for performing microscopic design study in architectural education in Malaysia. The methodology could also be extended to cover other fields of design in the country. This study recommends the use of protocol analysis methodology to provide empirical data from codification of subjective observations, hence, becoming a stepping stone for leveraging research on teaching and learning in architectural design studios in Malaysian universities.